U–Pb and fission‐track dating of a submarine pyroclastic rock from southwest Japan. (26th July 2017) - Ninomiya, Takashi; Taniguchi, Sho; Shimoyama, Shoichi; Watanabe, Koichiro; Danhara, Tohru; Iwano, Hideki; Dunkley, Daniel J.; Shiraishi, Kazuyuki; Gouzu, Chitaro
Abstract: The Okinoshima Formation crops out on Okinoshima Island and comprises a thick sequence (> 200 m) of pyroclastic rocks and alternating beds of sandstone and mudstone. Because Okinoshima Island is located between Honshu and Tsushima Island, the Okinoshima Formation potentially provides an important record of volcanism during the opening of the Japan Sea in northwest Kyushu, as well as a record of the formation of the present Genkai Sea region. In consideration of the lack of previous geochronological work, dating (fission‐track and U–Pb) of igneous zircons extracted from the Okinoshima Formation were undertaken and studied the clay mineral alteration in the pyroclastic material in order to reveal its thermal history. These data are used to constrain the age of the Okinoshima Formation and the present Genkai Sea region. Our results show that no thermal event has reset the fission‐track age after deposition of the pyroclastic rocks, and that the Okinoshima Formation was deposited at 16.2 Ma. The present Genkai Sea region is a deep‐sea basin, and its formation at 16.2 Ma was accompanied by submarine volcanism and rapid subsidence that marked the climactic stage of Japan Sea formation. After 16 Ma, the tectonic setting of the present Genkai Sea region changed from one of extension (related to the formation of the Japan Sea) to one of compression, with uplift occurring under the influence of the clockwise rotation of southwest Japan. Consequently, after 16 Ma the present Genkai Sea region became isolated from the forming processes of the Japan Sea. Abstract : The present Genkai Sea region is a deep‐sea basin, and its formation at 16.2 Ma was accompanied by submarine volcanism and rapid subsidence that marked the climactic stage of Japan Sea formation. However, after 16 Ma, the tectonic setting of the present Genkai Sea region changed from one of extension (related to the formation of the Japan Sea) to one of compression, with uplift occurring under the influence of the clockwise rotation of southwest Japan. Consequently, after 16 Ma the present Genkai Sea region became isolated from the processes that had been forming the Japan Sea.